Massive occurrence of heterotrophic filaments in acidified lakes: seasonal dynamics and composition - Vrba, Jaroslav; Nedoma, Jirí; Kohout, Leos; Kopácek, Jirí; Nedbalová, Linda; Rácková, Petra; Simek, Karel (FEMS microbiology ecology, 2003)
We documented permanent presence of heterotrophic filaments in three acidified lakes (pH<5) in the Bohemian Forest. Due to acidification, crustacean zooplankton were absent in all but one lake. In terms of carbon flow, microorganisms were thus almost exclusive players in the pelagic food webs. Variety of extremely long (>100 microm) heterotrophic filaments occurred in the lakes. The filaments usually accounted for >50% of total heterotrophic microbial biomass in the pelagic zone (medians of the total biomass: 82-108 microg C l(-1)), except for anoxic bottom layers and for episodic appearance of Daphnia longispina in one lake. Seasonal filament formation was mainly induced and maintained by grazing of mixotrophic flagellates (Dinobryon spp.) on small unicellular bacteria in the absence of cladoceran filtration. The filaments were less active than unicellular suspended bacteria. Fluorescence in situ hybridisation revealed that usually <50% of total bacteria were targeted with oligonucleotide probes for Eubacteria.